2011
DOI: 10.1002/stem.590
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function Controls Proliferation and Early Differentiation Potential of Embryonic Stem Cells

Abstract: Pluripotent stem cells hold significant promise in regenerative medicine due to their unlimited capacity for self-renewal, and potential to differentiate into any cell type of the body. In the current study, we demonstrate that proper mitochondrial function is essential for proliferation of undifferentiated embryonic stem cells (ESCs). Attenuating mitochondrial function under self-renewing conditions makes these cells more glycolytic-dependent, and is associated with an increase in the mRNA reserves of Nanog, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
234
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(251 citation statements)
references
References 38 publications
17
234
0
Order By: Relevance
“…This is in agreement with recent findings showing that mitochondrial OXPHOS is required for the proliferation of self-renewing hESCs [45,46]. On the other hand, iPSCs showed reduced levels of ATP reserve in comparison with hESCs.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with recent findings showing that mitochondrial OXPHOS is required for the proliferation of self-renewing hESCs [45,46]. On the other hand, iPSCs showed reduced levels of ATP reserve in comparison with hESCs.…”
Section: Discussionsupporting
confidence: 93%
“…Ample reports showed that the mitochondrial metabolism plays a pivotal role in stem cell proliferation and differentiation (Funes et al, 2007;Mandal et al, 2011;Xu et al, 2013). It is known that riboflavin and its cofactors are important components for mitochondrial metabolism (Hoppel and Tandler, 1975;Barile et al, 1997;Nelson and Cox, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more attention has been focused on mitochondria and cellular bioenergetics of stem cells, which has revealed their unique metabolic status [27][28][29]. It has been shown that mitochondrial activity or dormancy plays a major role in maintaining the undifferentiated state, whereas the proper activation and function of mitochondria is essential during the differentiation processes [29][30][31]. In addition, mitochondrial reactive oxygen species (ROS) regulate the differentiation of several stem cell types; and recently, ROS have been shown to inhibit adhesion of hMSCs to the site of injury [32][33][34].…”
Section: Introductionmentioning
confidence: 99%